Energy Conservation Guidebook - Patrick, Dale R.; Fardo, Stephen; Richardson, Ray E.; Patrick, Steven R. (Fairmont Press, Incorporated Taylor & Francis Group [distributor], 2007)
Annotation Emphasizing the systems approach to energy management, the Energy Conservation Guidebook, Second Edition covers the full scope of energy management techniques and applications for new and existing buildings. The book examines structural considerations, such as heat loss and gain, windows, and insulation. A thorough discussion of heating and cooling system optimization strategies is provided. Also covered are energy conservation measures for lighting systems, water systems, and electrical systems. Specific energy management applications are discussed in detail, including solar energy systems, energy management systems and alternative energy technologies.
Keywords: Energy conservation -- Handbooks, manuals, etc.; elektronické knihy; electronic books